Ethnomathematical insights from the tide-forecasting calendar of an Indonesian coastal community into mathematics classroom - Kusaeri, Al; Putrawangsa, Susilahudin; Prahmana, Rully Charitas Indra; Pardi, Muhamamad Habib Husnial; Idrus, Sayid Wahyu Alwi Sidik Al (Journal on Mathematics Education, 2025)
The integration of culturally embedded knowledge systems into mathematics education has gained scholarly interest in recent years; however, empirical research remains limited, particularly in the context of Indonesian coastal communities where traditional ecological knowledge is closely tied to astronomical and environmental cycles. Despite the growing prominence of ethnomathematics, there is a noticeable paucity of studies that systematically investigate the mathematical reasoning inherent in indigenous calendrical systems used for livelihood practices. Addressing this gap, the present study explores the ethnomathematical knowledge embedded in the calendrical practices of the Lungkak community in East Lombok, Indonesia. This system uniquely integrates local interpretations of the Pupuru (the Pleiades star cluster), lunar phases, the Hijri calendar, and the Gregorian calendar to predict seasonal transitions and tidal patterns crucial to artisanal fishing. Employing an ethnographic research design, data were gathered through purposive sampling, in-depth interviews, participant observation, and document analysis, and analyzed using interactive ethnographic techniques. The findings uncover sophisticated mathematical reasoning within the community’s calendrical system, including trigonometric concepts (angular relationships among celestial bodies), arithmetic and numerical sequences (predictive visibility patterns), modular arithmetic (cyclical astronomical forecasting), and set theory (classification of tidal phenomena). These insights reveal how formal mathematical concepts are embedded within cultural practices, demonstrating the community’s implicit engagement with abstract reasoning. This study contributes to the development of culturally responsive mathematics education by emphasizing the pedagogical value of integrating ethnomathematical content into classroom instruction. Such integration holds potential to enrich students’ mathematical literacy, foster contextual understanding, and support meaningful engagement with mathematical concepts through culturally relevant learning experiences.